The Urgency of Regulating the Investigative Authority of the Indonesian Air Force in the Enforcement of Law within the Indonesian Airspace Jurisdiction - Hafari, Abuzar; Nasution, Krisnadi; Hufron (Technium Social Sciences Journal, 2025)
This study aims to analyze the urgency of granting investigative authority to the Indonesian Military National Air Force (Tentara Nasional Indonesia Angkatan Udara TNI AU) in the enforcement of law within the national airspace, as well as to propose a legal framework that integrates the functions of national defense and criminal justice. The research employs a normative juridical method, utilizing statutory, conceptual, and comparative approaches. The legal materials used comprise both primary and secondary sources, collected through inventory, categorization, and doctrinal legal research. All legal materials were analyzed deductively through legal reasoning to address the research issues. The findings reveal the existence of a legal vacuum (absence of governing norms) regarding the investigative authority of the Air Force, which has consequently weakened law enforcement against airspace violations. This study proposes the establishment of a National Joint Air Investigation Unit (UGP) that integrates the Indonesian Military Air Force (TNI AU), the Indonesian National Police (Polri), and Civil Servant Investigators (PPNS) of the Ministry of Transportation. The study further asserts the necessity of granting limited investigative powers to the Air Force under civilian oversight, in order to reinforce national sovereignty and enhance the effectiveness of law enforcement within the Indonesian airspace jurisdiction.